On the unraveling of ‘revitalization of local health traditions’ in India: an ethnographic inquiry - Arima Mishra; Devaki Nambiar (International Journal for Equity in Health, 2018)
Abstract Background India has recently renewed emphasis on non-allopathic systems of medicine as a means to address the health needs of its populace. Earlier in 2002, its national health policy had sought to ‘revitalize’ community-based health knowledge and practices – jointly christened ‘local health traditions’. Yet policy texts remain silent on the actual means by which ‘revitalization of local health traditions’ should take place. Our research sought to understand the policy lessons of and for revitalization of local health traditions in the three Southern Indian states through an ethnographic inquiry in 2014–2016. Methods Our inquiry included a narrative synthesis of policy texts tracing the history of governance processes and mechanisms pertaining to traditional medicine, including local health traditions, linking this to the activities of non-governmental organizations (NGOs) and networks involved in “revitalization”. Through in-depth interviews, observations and case studies, we sought to understand the life worlds of local health tradition practitioners and what revitalization meant to them. Our method revealed that beyond a purely academic inquiry, we needed an (inter)action that would give greater voice to these perspectives and views leading to hosting an interactive dialogue among practitioners, NGO representatives, academics, and government officials. Results Our ethnographic inquiry unraveled the problematic of a litotic approach to local health traditions as those which are non- institutionalized, non-certified, non-documented; assuming the state to be the only source of power and legitimacy. Revitalization discussions were restricted (and often misled) by such an approach. Local health practitioners and others directed us to interesting possibilities of revitalization either through participatory modes of documentation of traditional health knowledge, strengthening existing collective forums for formal social recognition, and building pedagogical institutions that promote experiential learning. Conclusion Were we not enabled by ethnography as a method that changes its shape apace with emerging findings, we would have not been able to comprehensively answer our questions. This is critical because not only was this already a marginalized area of inquiry, but with any other method we risked reinforcing inequities by imposing epistemological and other hierarchies on our participants– whom we would argue were partners - in arriving at our conclusions.